Respuesta :

x^3-7x^2-5x+35

= x^2(x-7) - 5 (x-7)   now by definition 

=(x^2-5)(x-7)

hope this helps

Answer: Our final factorized form will be

[tex](x-\sqrt5)(x+\sqrt5)(x-7)[/tex]

Step-by-step explanation:

Since we have given that

[tex]x^3-7x^2-5x+35[/tex]

We need to factorize the expression by grouping :

[tex]x^3-7x^2-5x+35\\\\=x^2(x-7)-5(x-7)\\\\=(x^2-5)(x-7)[/tex]

Since we know that

[tex]a^2-b^2=(a+b)(a-b)[/tex]

so,

[tex]x^2-5=(x-\sqrt5)(x+\sqrt5)[/tex]

So, our final factorized form will be

[tex](x-\sqrt5)(x+\sqrt5)(x-7)[/tex]